2006
DOI: 10.1111/j.1468-1331.2006.01174.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma pneumoniae‐associated myelitis: a comprehensive review

Abstract: Myelitis is one of the most severe central nervous system complications seen in association with Mycoplasma pneumoniae infections and both acute transverse myelitis (ATM) as well as acute disseminated encephalomyelitis (ADEM) have been observed. We reviewed all available literature on cases of Mycoplasma spp. associated ATM as well as ADEM with dominant spinal cord pathology and classified those cases according to the strength of evidence implicating M. pneumoniae as the cause. A wide range of data on diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 94 publications
(372 reference statements)
1
41
0
2
Order By: Relevance
“…The few cases reported in the state of Rio Grande do Sul were diagnosed in the region of the municipality of Esteio [12], a place to which the patient was not exposed. Mycoplasma pneumoniae is a rare causal agent of TM, which manifests as a respiratory disease prior to the neurological status by roughly 10 days [13], and was not present in the present case study. Other possible infections were discarded, including the less common causes of MT, as influenza, measles, varicella, Lyme disease, German measles, and mumps.…”
Section: Discussionmentioning
confidence: 56%
“…The few cases reported in the state of Rio Grande do Sul were diagnosed in the region of the municipality of Esteio [12], a place to which the patient was not exposed. Mycoplasma pneumoniae is a rare causal agent of TM, which manifests as a respiratory disease prior to the neurological status by roughly 10 days [13], and was not present in the present case study. Other possible infections were discarded, including the less common causes of MT, as influenza, measles, varicella, Lyme disease, German measles, and mumps.…”
Section: Discussionmentioning
confidence: 56%
“…As in the case of acute disseminated encephalomyelitis, indirect immunological mechanisms such as immune complex-mediated injury leading to vasculopathy have been postulated as etiologies for transverse myelitis [Behan et al, 1986;Tsiodras et al, 2006]. As in acute disseminated encephalomyelitis, recent studies using polymerase chain reaction have reported the successful detection of the genome of M. pneumoniae in cerebrospinal fluid from patients with transverse myelitis [Abele-Horn et al, 1998;Goebels et al, 2001].…”
Section: Transverse Myelitismentioning
confidence: 99%
“…Neurological symptoms typically arise 1 to 2 weeks after a respiratory infection and they may be treated empirically with macrolide antibiotics, even though most macrolides penetrate the blood-brain barrier poorly, as well as with tetracycline and quinolones. There is some controversy concerning the need for antibiotic therapy since many mycoplasmal infections resolve spontaneously [8,[12][13][14][15]. Mycoplasma pneumoniae is the best-studied and perhaps the most frequent mycoplasma in neurological disease [8,11].…”
Section: Introductionmentioning
confidence: 99%